Pemberian Kompos Jerami Padi Terhadap Pertumbuhan dan Produksi Tanaman Jagung Manis (Zea mays saccharata Sturt) - Albert T.H. Samosir; Jeanne M. Paulus; Doortje M.F. Sumampow; Selvie Tumbelaka (COCOS, 2015)
ABSTRACT This research aims to study the application of Rice Straw Compost on Growth and Production of Sweet Corn ( Zea mays saccharata Sturt ) This study was conducted in the village of Tomohon sub district Taratara Dua West , Tomohon for 3 ( three ) months starting from the month of August to October  2014.  Experimentalwas design arranged in a Randomized Block Design (RBD), consisted of five treatments.It is treatment wasreplicated three times. The treatments waswhitout rice straw compost (K0), 5 ton/ha of rice straw compost (K1), 10 ton/ha of rice straw compost (K2), 15 ton/ha of rice straw compost (K3), and 20 ton/ha of rice straw compost (K4). Data was analysed using variance analysed Least Significant Difference ( LSD ) at level 5%. Results slowed that the treatment significantly effected on growth and production of sweet corn  ( Zea mays saccharata Sturt ) that were plant height, number of leaves , cob length, cobweight, but not significant to cob circle  effect  Keywords : Sweet Corn, Organic fertilizer